Seeking renewed relevance: Institutions of Nordic cooperation in the reform process - Christian Opitz; Tobias Etzold (Stiftung Wissenschaft und Politik (SWP), 2018)
Institutionalized Nordic cooperation is currently facing doubts about its political significance. Lately, the Nordic countries Denmark, Finland, Iceland, Norway and Sweden have experienced tensions and open differences of opinion which have hampered cooperation within the joint organizations. Against this background, the intergovernmental Nordic Council of Ministers, in particular, is currently undergoing a reform process aimed at re-establishing its political relevance. Although it is increasingly being institutionalized, particularly with regard to EU issues and sensitive political topics such as migration, Nordic cooperation is only gradually being substantially strengthened. Nevertheless, this realignment has the potential to secure the cooperation's future political relevance. Old and new bilateral and multilateral partnerships could contribute to this, especially those with Germany and the Baltic states.
Keywords: 320